Increased indoleamine 2,3-dioxygenase and quinolinic acid expression in microglia and müller cells of diabetic human and rodent retina - Hu, P.; Hunt, N.; Arfuso, Frank; Shaw, L.; Uddin, M.; Zhu, M.; Devasahayam, R.; Adamson, S.; Benson, V.; Chan-Ling, T.; Grant, M. (Association for Research in Vision and Ophthalmology, 2017)
© 2017 The Authors. PURPOSE. We investigated the relationship between inflammation, neuronal loss, and expression of indoleamine 2, 3-dioxygenase (IDO) and quinolinic acid (QUIN) in the retina of subjects with type 1 diabetes (T1D) and type 2 diabetes (T2D) and in the retina of rats with T1D. METHODS. Retinas from T1D (n = 7), T2D (n = 13), and 20 age-matched nondiabetic human donors and from T1D (n = 3) and control rats (n = 3) were examined using immunohistochemistry for IDO, QUIN, cluster of differentiation 39 (CD39), ionized calcium-binding adaptor molecule (Iba-1, for macrophages and microglia), Vimentin (VIM; for Müller cells), neuronal nuclei (NeuN; for neurons), and UEA1 lectin (for blood vessels). RESULTS. Based on morphologic criteria, CD39 + /ionized calcium binding adaptor molecule 1(Iba-1 + ) resident microglia and CD39 - /Iba-1 + bone marrow-derived macrophages were present at higher density in T1D (13% increase) and T2D (26% increase) human retinas when compared with controls. The density and brightness of IDO + microglia were increased in both T1D and T2D human retinas. The intensity of QUIN + expression on CD39 + microglia and VIM + Müller cells was greatly increased in both human T1D and T2D retinas. T1D retinas showed a 63% loss of NeuN + neurons and T2D retinas lost approximately 43% when compared with nondiabetic human retinas. Few QUIN + microglia-like cells were seen in nondiabetic retinas, but the numbers increased 18-fold in T1D and 7-fold in T2D in the central retina. In T1D rat retinas, the density of IDO + microglia increased 2.8-fold and brightness increased 2.1-fold when compared with controls. CONCLUSIONS. Our findings suggest that IDO and QUIN expression in the retinas of diabetic rats and humans could contribute to the neuronal degeneration that is characteristic of diabetic retinopathy.